2010
DOI: 10.1161/hypertensionaha.109.142646
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hypertension and Peripheral Inflammation by Reduction of Extracellular Superoxide Dismutase in the Central Nervous System

Abstract: Abstract-The circumventricular organs (CVOs) lack a well-formed blood-brain barrier and produce superoxide in response to angiotensin II and other hypertensive stimuli. This increase in central superoxide has been implicated in the regulation of blood pressure. The extracellular superoxide dismutase (SOD3) is highly expressed in cells associated with CVOs and particularly with tanycytes lining this region. To understand the role of SOD3 in the CVOs in blood pressure regulation, we performed intracerebroventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
128
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(140 citation statements)
references
References 35 publications
11
128
0
1
Order By: Relevance
“…Collectively, these data support our hypothesis that increased RAAS activity in hypertension exaggerates skeletal muscle contraction-evoked reflex sympathoexcitation by inducing oxidative stress in the muscle. Increased RAAS activity and developed oxidative stress are involved in the pathogenesis of hypertension (12,26,55) and are a hallmark in cardiovascular diseases that often develop from prolonged hypertension. In heart failure, we (19) have previously demonstrated that oxidative stress in the muscle plays a role in exaggerating the exercise pressor reflex.…”
Section: H148mentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these data support our hypothesis that increased RAAS activity in hypertension exaggerates skeletal muscle contraction-evoked reflex sympathoexcitation by inducing oxidative stress in the muscle. Increased RAAS activity and developed oxidative stress are involved in the pathogenesis of hypertension (12,26,55) and are a hallmark in cardiovascular diseases that often develop from prolonged hypertension. In heart failure, we (19) have previously demonstrated that oxidative stress in the muscle plays a role in exaggerating the exercise pressor reflex.…”
Section: H148mentioning
confidence: 99%
“…Moreover, this peptide has been known to activate NADPH oxidases, thereby triggering the production of superoxide and other reactive oxygen species (ROS) in various tissues, including skeletal muscle (13,41,51,55,57). The development of oxidative stress has also been implicated in the pathogenesis of hypertension (26,55). Superoxide functions in the neural process for encoding peripheral mechanical and thermal stimuli (18,25).…”
mentioning
confidence: 99%
“…ROS production in vessels, as well as other organs, including the heart, kidneys and brain, likely participate in blood pressure regulation. [30][31][32] This review will focus on ROS, the vascular system and hypertension, specifically relating to the clinical significance. All vascular cell types produce ROS, including endothelial, smooth muscle, adventitial fibroblasts and perivascular adipocytes, and can be formed by many enzymes, including xanthine oxidoreductase, uncoupled nitric oxide synthase, mitochondrial respiratory enzymes and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase [37][38][39][40][41][42][43][44] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 These results are supported by the recent reports that reduction of extracellular superoxide dismutase in the central nervous system promotes T-cell activation and vascular inflammation, modulates sympathetic outflow and induces hypertension. 14 It has also been found that active oxygen species and thromboxane A 2 reduced angiotensin-II type 2 receptor-induced vasorelaxation in diabetic rats. 15 Tumor necrosis factor-a has a function in activation of polymorphonuclear leukocyte NADPH oxidase, leading to systemic oxidative stress, inflammation and the development of hypertension.…”
mentioning
confidence: 98%
“…26 As the brain contains all components of the renin-angiotensin system, it is likely that low brain levels of DHA and EPA could enhance the level of angiotensin II, increasing the generation of free radicals and thereby accelerating the development of hypertension. [9][10][11][12][13][14][15][16] AA, EPA and DHA can also form precursors to anti-inflammatory compounds such as lipoxins, resolvins, protectins, maresins and nitrolipids (see Figure 1 for the metabolism of essential fatty acids) that suppress leukocyte activation, inhibit free radical generation and pro-inflammatory cytokine production, enhance NO generation and exhibit potent anti-inflammatory effects. 26,27 Hence, whenever DHA (and probably other fatty acids such as AA and EPA) levels are low in the brain (especially in the hypothalamus), the production of lipoxins, resolvins, protectins, maresins and nitrolipids will be low as well, resulting in inflammation (as a result of increased production of tumor necrosis factor-a) and the induction of hypertension.…”
mentioning
confidence: 99%